KONFLIK ANTARA PEMERINTAH PROVINSI DKI JAKARTA DAN PEMERINTAH KOTA BEKASI DALAM PENGELOLAAN SAMPAH BANTAR GEBANG TAHUN 2015-2016 - Aninda Ishar, Dheevanadea Primantariputri; Sardini, Nur Hidayat; Astrika, Lusia (Journal of Politic and Government Studies, 2017)
The problem of waste is endless and has become a serious problem especially in big cities. With greater conditions and increased demand for waste collection on one side, and the limited land for waste management on the other, it requires the DKI Jakarta Government to cooperate with other areas in the vicinity. Therefore the Provincial Government of DKI Jakarta in cooperation with the City Government of Bekasi work together for waste management, the Provincial Government of DKI Jakarta bought land in the Bekasi City to be a Final Disposal Place, and over time turned into Integrated Waste Disposal Sites. In cooperation, there is a conflict between the Provincial Government of DKI Jakarta with the Bekasi City Government related to waste management, and conflict occurred in 2015 to 2016.The research method used in this research is qualitative research method with data collection technique that is interview, literature study, and documentation. The informants in this study were Chairman of DPRD Commission A of Bekasi City, Head of DKI Jakarta Environment Agency, Head of Integrated Waste Management Unit of DKI Jakarta Environment Agency and residents around Bantar Gebang.The result of this research is found the cause of conflict happened, there are 4 causes and there is: 1) Bekasi City Government feels the Jakarta Government has committed a breach of cooperation agreement, which becomes the main trigger issue is a violation of the garbage truck route that eventually open the other violations. 2) The reaction of Jakarta Governor Basuki T. Purnama who seemed arrogant to the Bekasi DPRD made the conflict heated up. 3) DKI Jakarta Provincial Government feel the cause of all this because of the default done by a third party that is PT. Godang Tua Jaya. 4) Residents who feel disadvantaged starting to close the road to Bantar Gebang and ultimately the citizens shut Bantar Gebang in June 2017, the citizens reject self-managed Bantar Gebang because they are afraid of the future of waste management is not going wellIn the settlement of the conflict, a meeting between the Provincial Government of DKI Jakarta and the City Government of Bekasi discussed the proposed amendment. Jakarta Goverment needs to deal with the waste problem from the root ranging from waste reduction were transported to Bantar Gebang and realization of the ITF, which is planned to be built to process the waste in Jakarta, because the waste problem is not going to stop because waste disposal is done in other cities although the land is owned by DKI Jakarta.Keywords: Inter-regional Conflict, Waste Management